Giant scalp arteriovenous malformation - WORM,PAULO VALDECI (2016)
SUMMARY Arteriovenous malformations (AVMs) of the scalp are rare lesions. The clinical picture presents with complaints of increased scalp, scalp disfigurement, pain and neurological symptoms. Its origin can be congenital or traumatic. We present a case of giant scalp AVMs and its management, followed by a brief literature review on the subject. The diagnosis of scalp AVMs is based on physical examination and confirmed by internal and external carotid angiography or computed tomographic angiography (CTA). Surgical excision is especially effective in scalp AVMs, and is the most frequently used treatment modality.